(untitled) (Jurnal Teknologi (Sciences & Engineering), 2018)
A series of mesoporous ZnO/TiO2 composites were successfully synthesized using cetyltrimethylammonium bromide surfactant. The composites of different Zn:Ti molar ratios (0.5:1, 0.75:1, and 1:1) were prepared by impregnating ZnO onto mesoporous TiO2. XRD results verified co-existence of both anatase TiO2 and hexagonal wurtzite ZnO in the ZnO/TiO2 composites. Based on the Tauc plots, all the composites showed almost the same band gap energy of approximately 3.21 eV. The fourier transform infrared spectroscopy results successful covering of ZnO on the surface of the TiO2 as the hydrophilicity property of TiO2 decreased remarkably with the loading of ZnO in the composites. N2 adsorption-desorption isotherms of the samples exhibited type-IV isotherm with a hysteresis loop. The Barrett-Joyner-Halenda pore size distribution revealed that the average pore size of the composites was around 3.6 nm, indicating the formation of mesopores dominantly in the samples. The photocatalytic removal of phenol over the samples under UV light irradiation after 3 h decreased in the order: ZnO/TiO2 composites > anatase TiO2 (with surfactant) > anatase TiO2 (without surfactant) > ZnO. The composite with Zn:Ti molar ratio of 0.75:1 has achieved the highest photocatalytic activity of 36.5% in the removal of phenol under UV light irradiation for 3 h.